(untitled) (Scientific Journal of Actuarial Finance and Accounting, 2026)
This study analyzes the structural integration of Islamic microfinance into Uzbekistan’s dualistic financial system following the 2024 CBU regulatory reforms. Using empirical data from the Central Bank’s 2024 Annual Report, the research evaluates the distribution of Shariah-compliant instruments through the lens of "Incremental Implementation" theory. The results identify a profound contractual concentration: Murabaha dominates the market with a 99.34% share (1,117.0 million UZS), while Ijarah accounts for only 0.66%, and participatory models (Musharaka) remain unused. This "contractual skew" indicates that while the system successfully mobilizes dormant capital, it remains focused on retail consumption rather than production-based risk-sharing. The study concludes that to achieve the "Uzbekistan – 2030" goals, the ecosystem must transition from trade-based installments to digitalized equity models. "Fintech-ization" is identified as the key driver for diversifying the dualistic model and supporting sustainable SME growth.